Urban Revitalisation for a City's Soul: The Case of Kampong Bharu - Halimaton Saadiah Hashim,; Sarah Aziz,; Nik Mohd Ruiz Razy, (Kajian Malaysia, 2017)
It is an accepted dogma by urban planning gurus that livable and sustainable cities, neighbourhoods and communities are those with souls that differ according to the communities' socio-cultural, economic, political and physical environments and perspectives. The soul of a city is in its people. This article presents findings from a study on the revitalisation of Kampong Bharu. Being only a conceptual study, the findings are only based on literature review, observations through walkabouts and drive-throughs, and interviews with custodians and major stakeholders. The article presents the results of the conceptual study: the concept of a city's soul in urban planning, the urban village concept, history and characteristics of Kampong Bharu the urban village, manifestations of its soul. The article will also present key issues in revitalising Kampong Bharu that is, custodians, mandates and institutional arrangement, heritage-led development, and a brief assessment of actions in urban heritage conservation and revitalising of Kampong Bharu's soul. The study concludes by supporting the move to revitalise Kampong Bharu and its soul. However, a deeper research is recommended to untangle the conundrum created by its legal and institutional arrangements; establishing a formal definition of Kampong Bharu's soul; the development of a set of criteria for planning a heritage-led development; and cataloging tangible and intangible Malay cultural elements in Kampong Bharu.